(untitled) (Annals of Medical Research, 2024)
Aim: Systemic Immune-Inflammatory Index (SII) is an index that assesses the systemic inflammatory response and has been increasingly used in recent times. The objective of this study is to evaluate the role of systemic inflammation in alopecia areata (AA) by examining the SII and to investigate its relationship with disease severity. Materials and Methods: This is a retrospective study in which SALT (Severity of Alopecia Tool) scores, SII values, and neutrophil-to-lymphocyte ratios (NLR) of patients diagnosed with AA and followed up at our clinic between January 2023 and March 2024 were evaluated. Results: The study included a total of 153 patients with AA (99 males and 54 females) and 91 healthy controls. NLR in the patient group (2.24 ± 0.64) was significantly higher than in the control group (2.04 ± 0.54) (p = 0.013). SII in the patient group (593.38 ± 214.25) was also significantly higher than in the control group (497.26 ± 154.72) (p = 0.001). There was a significant positive, correlation between the SALT score and the NLR (p = 0.001). Similarly, there was a significant positive correlation between the SALT score and the SII (p = 0.001). The SII for the group with alopecia universalis was significantly higher than for other patient groups (p = 0.001). There was a positive, statistically significant relationship between disease duration and both the NLR and SII (p = 0.001 and p = 0.001). Conclusion: We observed elevated inflammatory parameters suggesting systemic inflammation in patients with AA. The NLR and SII were both higher in the patient group compared to the control group. Additionally, as the SALT score, increased, so did the levels of NLR and SII. We concluded that in addition to its diagnostic utility in AA, SII also serves as a biomarker that correlates with disease severity.